2021
DOI: 10.1021/acsomega.1c04460
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Adsorption Properties of Soybean Dreg/Hydrocalumite Composites

Abstract: The application of biomass-based composites in the field of adsorption has attracted extensive attention. Herein, soybean dreg/hydrocalumite composites were prepared by in situ self-assembly from soybean dregs and applied to the adsorption of Congo Red (CR). The composites were characterized by scanning electron microscopy, X-ray diffraction, Fourier infrared spectroscopy, and N2 physical adsorption–desorption. The results showed that the adsorption property of soybean dregs/hydrocalumite for CR was better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The peaks at 29.4, 35.9, 46.7, and 49.9° indicated that there was a small amount of CaCO 3 in LDH and 5% BD–LDH2. 5 , 19 , 21 However, the crystal surface of cellulose was not obvious in the spectrum of 5% BD–LDH2, which was mainly due to the low content and uniform dispersion of BD. Compared with LDH, the characteristic diffraction peak intensity of the LDH phase in 5% BD–LDH2 was greatly weakened, which might be due to the reduction particle size or crystallinity of the LDH sheet in 5% BD–LDH2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The peaks at 29.4, 35.9, 46.7, and 49.9° indicated that there was a small amount of CaCO 3 in LDH and 5% BD–LDH2. 5 , 19 , 21 However, the crystal surface of cellulose was not obvious in the spectrum of 5% BD–LDH2, which was mainly due to the low content and uniform dispersion of BD. Compared with LDH, the characteristic diffraction peak intensity of the LDH phase in 5% BD–LDH2 was greatly weakened, which might be due to the reduction particle size or crystallinity of the LDH sheet in 5% BD–LDH2.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with LDH, the characteristic diffraction peak intensity of the LDH phase in 5% BD–LDH2 was greatly weakened, which might be due to the reduction particle size or crystallinity of the LDH sheet in 5% BD–LDH2. 21 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations